Optimal Portfolio Choice in a General Equilibrium Model with Portfolio Frictions and Short-Selling Constraint - Simon Tièche; Didier Cossin (Mathematics)
Recent developments in dynamic portfolio optimization have focused on the role played by portfolio frictions. Portfolio frictions make the portfolio’s response to financial shocks weaker and more gradual than in a model without frictions. At the same time, institutional investors are prevented from short-selling, a situation in which investors are restricted from taking negative positions in an asset, while other types of investors can short-sell. However, the literature has not yet discussed the implication of a short-selling constraint in a model of optimal portfolio choice with frictions. We solve a general equilibrium model of portfolio choice with frictions and a short-selling constraint. The model features investors who own firms and allocate capital across firms, households who work in the firms and earn revenues, and firms that produce the final good using capital and labor and redistribute profits to investors. We show the conditions under which negative financial conditions reduce the optimal share invested in a firm to zero. Finally, we simulate the model to show that the short-selling constraint prevents investors from amplifying financial shocks, which leads to a more stable business cycle. Our results are important for financial regulators as they suggest forbidding short-selling.